Pengamatan In-Situ Tekanan dan Temperatur pada Pembentukan MgH2/Ni melalui Metode Reactive Mechanical Alloying (RMA) untuk Aplikasi Material Penyimpan Hidrogen - Erfan Handoko; Aditia Pradipta; Bambang Soegijono; Zulkarnain Jalil (Department of Physics, Sebelas Maret University, 2017)
The observation on reactive mechanical alloying (RMA) process had been done to form MgH2 material with adding Ni nanoparticles as catalist for hydrogen storage material applications. Pressure and temperature of material forming were recorded by microcontroller set for 30 minutes. Mg with adding Ni 5 wt % was milled by High Energy Ball Mill (HEBM) at H2 atmosphere in 1 atm of pressure. The measurement results showed that the pressure had been changed and temperature also changes up to 38oC. This process proves that the alloying betwen Mg and H2 had been formed. The X-ray diffraction pattern identify MgH2 phase. SEM image showed the morphology of MgH2 particles.